Enhancing Agroforestry Residual Biomass Recovery: Developing and Validating a Supply Chain Management App-Based Model - Bastos, Tiago; Nunes, Leonel; Teixeira, Leonor (International Journal of Industrial Engineering and Management, 2025)
Due to climate change and changes in agricultural activities, there has been an upward trend in the area burned in Mediterranean countries. In addition, some fires arise because of negligent attitudes with fire, often used to eradicating certain leftovers from forestry and agricultural activities. As a way of dealing with this type of incident and therefore reducing the occurrence of rural fires, there is a need to create destinations for these leftovers, promoting the recovery of residual biomass. In an age of the internet and digital applications, their use can be used as a driver to fill this need for a destination for leftovers, connecting the two sides of the market, the supply, and the demand. In this context, the purpose of this study is to consolidate an app-based model already presented in previous studies, using experts’ validation. As results, this work proposes a complete version of the possible models/scenarios that the recovery of agroforestry leftovers can take. In addition, this study also presents a more consolidated requirements list for the app that will support these models. Article history: Received (June 17, 2024); Revised (December 4, 2024); Accepted (January 4, 2025); Published online (March 17, 2025)